The Correlation Between Serum Glucagon Peptide-1 Levels with Intima Media Thickness of Carotid Artery in Type 2 Diabetes Mellitus - Puspita Sari, Maya; Kusnadi , Yulianto; Indrajaya, Taufik (Riviera Publishing, 2023)
Type 2 Diabetes Mellitus is a group of metabolic disorders characterized by clinical hyperglycemia due to defects in insulin secretion, insulin action or both. This study was to determine the correlation between serum fasting Glucagon Like Peptide-1 (fGLP-1) levels and serum 1 hour post prandial Glucagon Like Peptide-1 (1hGLP-1) levels with IMT of carotid artery in patients with Type 2 DM. This study used a correlative analytic with a cross-sectional approach in population of Type 2 DM patients who were treated at the Interna Polyclinic at Dr. Mohammad Hoesin Palembang the IMT of carotid artery was measured with a high-resolution carotid doppler ultrasound B-mode ultrasound machine. The GLP-1 level was measured by the ELISA method. There were 40 subjects with a median age of 52 (40-59) years. A strong negative correlation was found between fGLP-1 serum levels and IMT of carotid artery with r= -0.748; p = 0.000; n=40. This study also found a strong negative correlation between serum levels of 1hGLP-1 and carotid IMT with r = -0.600; p = 0.000; n=40. There is a strong correlation between serum fGLP-1 levels and serum 1hGLP-1 levels with IMT of carotid artery in Type 2 DM patients. Measurement of serum levels of fGLP-1 and 1hGLP-1 may be an important indicator in evaluating cardiovascular risk in Type 2 DM patients. It may also provide guidance in the development of therapies for Type 2 DM patients to reduce the risk of cardiovascular disease.